NEED OF MULTILINGUAL EDUCATION IN PRIMARY EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
Multilingual education, particularly at the primary level, is increasingly recognized as a vital component of a holistic and inclusive education system. In a diverse world where multiple languages coexist, equipping children with the ability to navigate different linguistic landscapes fosters not only cognitive development but also social cohesion. This thematic paper explores the need for multilingual education in primary education, delving into its various dimensions, including its definition, importance, benefits, and the role it plays in child development. With globalization creating an interconnected world, and with countries like India and many others having multiple official languages, it is imperative that educational systems adapt to these realities by integrating multilingual approaches from an early stage.The paper first defines multilingual education and its application within the primary school framework, focusing on how it promotes better learning outcomes and prepares children for future educational and professional opportunities. The need for multilingual education is examined through the lenses of cultural identity, social inclusion, and cognitive benefits, supported by research on how early exposure to multiple languages enhances brain development and language acquisition. Additionally, this paper highlights the wide-ranging benefits of multilingual education, such as improved problem-solving skills, enhanced creativity, and greater cultural empathy.